Innovation Strategies: A Case Study of Leading Philippine Corporations - Ayo, Eliza B.; Tamayo, Josan D.; Flores, Joever Joseph C.; Xiao, Yao (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
Innovation is pivotal for corporate sustainability in competitive emerging markets. This study examines the innovation management strategies of leading Philippine corporations in finance, real estate, retail, and technology from 2020 to 2024, utilizing the Input-Process-Output-Outcome (IPOO) framework, which maps how inputs are transformed into processes, outputs, and outcomes. Through qualitative content analysis of corporate reports and industry publications, we identify context-specific strategies, such as digital transformation (e.g., online platforms), sustainability initiatives (e.g., carbon neutrality), and customer-centric approaches (e.g., AI-driven tools), as key drivers of growth. For instance, SM Prime Holdings achieved a 14% net income increase in 2024 through sustainable mall expansions (SM Prime, 2024), while BDO Unibank’s AI-driven tools enhanced customer engagement by an estimated 20% (based on corporate reports). The study contributes to innovation management literature by demonstrating how these strategies drive financial and environmental outcomes in emerging markets, offering insights for policymakers and business leaders.